Matchmaking Bureau at the Ministry of Religious Affairs of Surakarta: The Legal Utilitarianism Perspective on the Samawa Program - Utami, Ria Cahyaning; Hilmy, Ahmad Arif Masdar; Al Adawiyah, Mutiah Robiah (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2023)
Non-governmental entities often facilitate current matchmaking trends, promoting certain ideologies that may contradict the Islamic family law model introduced by the state. In response, Surakarta’s Ministry of Religious Affairs launched the "Samawa Program: Make Me Your Partner" to support matchmaking, especially amid limited mobility during the COVID-19 pandemic. This article uses a philosophical approach to examine this program’s goals, rules, and strategies and how it aligns with Jeremy Bentham’s legal utilitarianism theory. The article finds that this free of charge program provides marriage guidance practices distinct from regular marriage counseling practices at the Office of Religious Affairs. The program’s objective is for individuals to get marriage guidance as a foundation for building a family and to find a partner who meets their criteria. Considering Bentham’s seven indicators of happiness and pain levels, the program fully satisfies the intensity, duration, proximity, and fecundity benefit aspects. However, it can potentially generate harm regarding the other three elements: certainty, purity, and extent. At this stage, the program is considered highly beneficial, serving as an effective facilitation tool for individuals seeking compatible partners. It not only ensures a satisfying matchmaking experience but also provides quick, credible access to essential marital knowledge.